2020
DOI: 10.1016/j.insmatheco.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Is the inf-convolution of law-invariant preferences law-invariant?

Abstract: We analyze the question of whether the inf-convolution of law-invariant risk functionals (preferences) is still law-invariant. In other words, we try to understand whether the representative economic agent (after risk redistribution) only cares about the distribution of the total risk, assuming all individual agents do so. Although the answer to the above question seems to be affirmative for many examples of commonly used risk functionals in the literature, the situation becomes delicate without assuming speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, the right-hand term can be strictly greater than the arbitrary ǫ > 0 in the definition of uniform continuity. Nonetheless, Lemma 1 in (Liu et al, 2020) shows that uniform continuity is preserved when I is finite, whereas Example 6 in that paper provides a case where ordinary continuity is not preserved.…”
Section: We Use the Notations {Xmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the right-hand term can be strictly greater than the arbitrary ǫ > 0 in the definition of uniform continuity. Nonetheless, Lemma 1 in (Liu et al, 2020) shows that uniform continuity is preserved when I is finite, whereas Example 6 in that paper provides a case where ordinary continuity is not preserved.…”
Section: We Use the Notations {Xmentioning
confidence: 89%
“…(ii) Liu et al (2020) showed that, in the usual case of finite I, law invariance is preserved under other continuity conditions that primarily rely on the existence of countable iid uniform random variables, which is always the case for atomless spaces. However, we are unable to extend their result, as in our framework, arbitrarily many such random variables would be required.…”
Section: We Use the Notations {Xmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, most concrete risk measures (such as Value-at-risk, Expected shortfall, Haezendonck-Goovaerts risk measures) and special classes of risk measures (such as distortion and quantile-based risk measures) are indeed law invariant. Research on general law-invariant risk measures has been intense and has produced many profound results; see, e.g., Bellini et al [4,5], Chen et al [10], Filipović and Svindland [16,17], Gao et al [20], Jouini et al [22,23], Krätschmer et al [24], Kusuoka [25], Liu et al [27], Wang and Zitikis [35], and Weber [36].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, law-invariant risk measures have been of intense research interest in Financial Mathematics; see, e.g., [2,3,5,7,8,10,12,13,14,15,17,19,20,21,22]. Of particular interest to us are two recent papers [3,11] that investigate when a law-invariant risk measure collapses to the mean, i.e., being a scalar multiple of expectation.…”
Section: Introduction and Notationmentioning
confidence: 99%